Report of the Grow More Food Enquiry Committee - Ministry of Food and Agriculture, Government of India (Ministry of Food and Agriculture, Government of India, 1952)
The Committee was appointed by the Government of India, Ministry of Food & Agriculture, in its Resolution No. F.l-2/52—GS(P), dated the 8th February, 1952 (reproduced as Appendix I) with the following terms of reference:— to examine the categories of G.M.F. schemes for which funds have been sanctioned and the extent to which the utilisation of the funds has been in conformity with the intended purposes; to assess the relative efficiency of the different categories of schemes for increasing food production in the context of the available means and the prevalent agricultural practices, particularly with respect to the use of fertilisers, compost and improved seeds, and taking into account the lag between the grant of money and the actual production of the crop; to enquire whether the follow-up arrangements for demonstrating and teaching the cultivators have been properly organised in the areas in which G.M.F. funds have been spent.
Ministry of Food and Agriculture
Government of India Ministry of Food and Agriculture